Manganese oxide-based nanocomposite electrodes for supercapacitors / Siti Rohana Majid - Siti Rohana, Majid (2016)
The increasing demands on energy have led to environmental issues and the depletion of fossil fuels. The intense research on energy storage and conversion has attracted much attention for future technology development. Batteries have become a choice for energy storage devices in many applications. However, expanding markets are pushing for alternative pulse batteries that offer high power and long cycle life. Inspired by this, supercapacitors have attracted growing interest due to their high power density, long cycle life, and fast charging rate, which display great potential in complimenting or even replacing batteries in many applications. The research work in this project concentrates on improving the specific capacitance or energy density of nanostructure composite metal oxides electrodes, namely oxides of manganese, nickel and cobalt (MnO2, MnO2/NiO and Mn3O4/NiO/Co3O4) with porous texture morphology. First, MnO2 was deposited on top of stainless steel by simple chronopotentiometry electrodeposition method with various manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O) concentrations in deposition solution. The optimum performance was obtained using 0.01 M Mn(CH3COO)2·4H2O. In order to enhance the specific capacitance of MnO2 electrode, the NiO was incorporated into the MnO2 electrode by adding different concentrations of nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O) mixed with 0.01 M Mn(CH3COO)2·4H2O. The optimum performance of MnO2-NiO electrode was obtained using the deposition solution containing 0.25 M Ni(CH3COO)2·4H2O mixed with 0.01 M Mn(CH3COO)2·4H2O. The optimum MnO2-NiO electrode was further studied in different electrodeposition modes and different CV’s cycles. The work proceeded by adding different concentrations of cobalt ion into 0.01 M Mn(CH3COO)2·4H2O mixed with 0.25 M Ni(CH3COO)2·4H2O concentration. The iv effect of the addition of different cobalt ion concentrations was explored and the obtained Mn3O4-NiO-Co3O4 ternary electrode exhibited optimum specific capacitance of 7404 F g-1 with high energy and power density of 1028 Wh kg-1 and 99 kW kg-1 respectively at current density of 20 A g-1 in 0.5 M potassium hydroxide (KOH)/0.04 M potassium ferrocyanide (K3Fe(CN)6) mixture electrolyte. Lastly, the electrochemical performance of supercapacitors were enhanced by incorporating MnO2 electrode with carbon based composite (reduce graphene oxide (RGO)/glucose carbon). The incorporation of RGO/glucose carbon into MnO2 electrode increased the electrical conductivity of the electrode. The introduction of D (+) glucose into the deposition solution slowed down the nucleation process of MnO2 particles and led to uniform and ultrathin nanoflakes structure. The optimized electrode exhibited low transfer resistance and resulted in excellent electrochemical performance in three electrolyte systems viz. sodium sulfate (Na2SO4), KOH and KOH/K3Fe(CN)6 electrolytes. The optimum specific capacitance obtained was 13,333 F g-1 with energy density and power density of 1851 Wh kg-1 and 68 kW kg-1 respectively at current density of 20 A g-1 in mixed 0.5 M KOH/0.04 M K3Fe(CN)6 electrolyte. The preparation of electrodes in this work using electrodeposition method is simple, low-cost, and environmental-friendly. It holds great potential to produce cost-effective and high energy density supercapacitors.